Knowledge, opinions and attitudes of primary care physicians about generic drugs: a cross-sectional study. (19th December 2020) - Oncu, Seyma; Bayram, Dilara; Aydin, Volkan; Isli, Fatma; Aksoy, Mesil; Akici, Ahmet; Ucku, Reyhan; Gelal, Ayse
Abstract: Background: Generic drug (GD) use is affected by many factors, including physicians' approach. Objective: This study aimed to investigate the knowledge, opinions and attitudes of primary care physicians (PCPs) about GDs and potentially associated factors. Methods: An adequately representative sample ( n = 354) of PCPs was determined via stratified and simple random sample selection method in this descriptive, cross-sectional study. The research data were collected through a face-to-face 40-item survey, where the knowledge, opinions and attitudes about GDs were questioned. The prescribing percentage of GDs overall was also examined. Results: The survey was completed by 305 PCPs (mean age: 49.2 ± 7.9 years; 57.4% male). The rate of correct responses about GDs was 67.6% for basic knowledge and 46.6% for the development process. The percentages of PCPs who declared that GDs were 'less efficacious', 'of lower quality' and 'less safe' than original drugs were 65.2%, 53.4% and 35.4%, respectively. More than half (60.3%) of the PCPs declared not to pay attention to whether the drug is generic while prescribing. It was observed that, as the knowledge level of the physicians increased, negative opinions and prescribing attitudes regarding the effectiveness, quality and safety of the GDs decreased. The rate of GD prescribing (51.6%) in Izmir was lower than the rest of the country (54.6%; P < 0.001). Conclusion: This study shows that the knowledge of PCPs about GDs is generally inadequate, which reflects negatively on their opinions and attitudes regarding the use of GDs. Educational activities can help establish awareness that GDs can be used without doubt of their effectiveness, quality and safety.